Determining the Theory of Planned Behavior's Predictive Power on Adolescents' Dependence on Computer Games - Ali Vafaeenajar; Maryam Masihabadi; Mehdi Moshki; Hosein Ebrahimipour; Hadi Tehrani; Habibollah Esmaily; mitra dogonchi (Iranian Association of Health Education and Health Promotion, 2015)
Background and objective: The most important psychological-social effect of computer games is their dependence and this can not only lead to financial problems, but can also lead to the appearance of some problems in school and in social communications with other people throughout life. Thus, the present study was done with the aim of determining the predictive power of the theory of planned behavior upon dependence to computer games among teenagers. Methods: In this descriptive-analytical study 300 teenagers referring to affiliated playing clubs that were diagnosed, in the first stage of the study to be depended on computer games, were randomly selected. Data were collected through a researcher-made questionnaire consistent with the theory of planned behavior constructs and adolescents Gaming Dependence Questionnaire (GAS). The data were analyzed using t tests, regression, Mann-Whitney, chi-square test. Results: Median age of participants was 15. Regression results showed that the perceived of behavioral control (p<0.001), attitude (p<0.001) had predictable insight. And prognosticated consciousness of game dependence and that they intended to use games. Among the demographic variables, age, type of admission to clubs played, the number of hours of play during the week and the time referring to playing clubs, 96% of the variance in gaming dependency predictions was for their target population. Conclusion: The theory of planned behavior could predict the bulk of computer games. The results suggest that the use of the theory of planned behavior, focusing on attitudes and perceived behavioral control in educational interventions, can bring effective results. Paper Type: Research Article.